Preimplantation genetic testing for more than one genetic condition: clinical and ethical considerations and dilemmas. Issue 6 (23rd May 2019) - van der Schoot, V; Dondorp, W; Dreesen, J C F M; Coonen, E; Paulussen, A D C; de Wert, G; de Die-Smulders, C E M
Abstract: STUDY QUESTION: Which clinical and ethical aspects of preimplantation genetic testing for monogenic disorders or structural rearrangements (PGT-M, PGT-SR) should be considered when accepting requests and counselling couples for PGT when applied for more than one condition (combination-PGT; cPGT-M/SR)? SUMMARY ANSWER: cPGT is a feasible extension of the practice of PGT-M/SR that may require adapting the criteria many countries have in place with regard to indications-setting for PGT-M/SR, while leading to complex choices that require timely counselling and information. WHAT IS KNOWN ALREADY: Although PGT-M/SR is usually performed to prevent transmission of one disorder, requests for PGT-M/SR for more than one condition (cPGT-M/SR) are becoming less exceptional. However, knowledge about implications for a responsible application of such treatments is lacking. STUDY DESIGN, SIZE, DURATION: Retrospective review of all (40) PGT-M/SR applications concerning more than one genetic condition over the period 1995–2018 in the files of the Dutch national PGT centre. This comprises all relevant national data since the start of PGT in the Netherlands. PARTICIPANTS/MATERIALS, SETTING AND METHODS: Data regarding cPGT-M/SR cases were collected by means of reviewing medical files of couples applying for cPGT-M/SR. Ethical challenges arising with cPGT-M/SR were explored against the background of PGT-M/SR regulations in several European countries, as well as of relevant ESHRE-guidance regarding both indications-setting and transfer-decisions. MAIN RESULTS AND THE ROLE OF CHANCE: We report 40 couples applying for cPGT-M/SR of which 16 couples started their IVF treatment. Together they underwent 39 IVF cycles leading to the birth of five healthy children. Of the couples applying for cPGT, 45% differentiated between a primary and secondary condition in terms of perceived severity. In the light of an altered balance of benefits and drawbacks, we argue the 'high risk of a serious condition' standard that many countries uphold as governing indications-setting, should be lowered for secondary conditions in couples who already have an indication for PGT-M/SR. As a consequence of cPGT, professionals will more often be confronted with requests for transferring embryos known to be affected with a condition that they were tested for. In line with ESHRE guidance, such transfers may well be acceptable, on the condition of avoiding a high risk of a child with a seriously diminished quality of life. LIMITATIONS, REASONS FOR CAUTION: We are the first to give an overview of cPGT-M/SR treatments. Retrospective analysis was performed using national data, possibly not reflecting current trends worldwide. WIDER IMPLICATIONS OF THE FINDINGS: Our observations have led to recommendations for cPGT-M/SR that may add to centre policy making and to the formulation of professional guidelines. Given that the introduction of generic methods for genomic analysis in PGT will regularly yield incidental findings leading to transfer requests with these same challenges, the importance of our discussion exceeds the present discussion of cPGT. STUDY FUNDING/COMPETING INTEREST(S): The research for this publication was funded by the Dutch Organization for Health Research and Development (ZonMw), project number: 141111002 (Long term safety, quality and ethics of Preimplantation Genetic Diagnosis). None of the authors has any competing interests to declare.